Methyltransferase DNMT3B promotes colorectal cancer cell proliferation by inhibiting PLCG2 - Ji Yong; Wang Yang; Zou Jiacheng; Liu Guanghao; Xia Mingyu; Ren Jun; Wang Daorong (Acta Biochimica et Biophysica Sinica)
Aberrant DNA methylation patterns in the promoter region of PLCG2 are associated with dysregulated signaling pathways and cellular functions. Its role in colorectal cancer cells is still unknown. In this study, qRT-PCR is used to measure DNMT3B expression in colorectal cancer. Western blot analysis and immunohistochemistry are used to analyze DNMT3B and PLCG2 protein levels in colorectal tissues and cell lines. Cell Counting Kit-8 (CCK-8) and colony formation assays are used to assess the proliferation of colorectal cancer cells. Methylation-specific PCR (MSP) and bisulfite-sequencing PCR (BSP) are used to measure DNA methylation level. Our results show that DNMT3B is overexpressed in colorectal cells in the TCGA datasets according to Kaplan-Meier plots. DNMT3B is significantly overexpressed in tumor tissues compared to that in adjacent nontumor tissues. Western blot analysis results demonstrate high expression of DNMT3B in tumor tissues. Compared to normal colonic epithelial cells, colorectal cancer cell lines exhibit elevated level of PLCG2 methylation. Overexpression of PLCG2 effectively prevents the growth of colorectal cancer xenograft tumors in vivo. PLCG2 is identified as a key downstream regulatory protein of DNMT3B in colorectal cancer. DNMT3B inhibits PLCG2 transcription through methylation of the PLCG2 promoter region. DNMT3B controls colorectal cancer cell proliferation through PLCG2, which is useful for developing therapeutic approaches that target PLCG2 expression for the treatment of colorectal cancer.